Planning procedures involved in teamteaching and how to maximize potentials - Hildebrand, Elke; Ruess, Annemarie; Stommel, Sarah; Brühlmann, Olga (Swiss Journal of Educational Research, 2017)
Due to restructured educational policies, teamteaching is increasingly becoming a daily routine for teachers in Swiss schools. As teamteaching has great potential, it is of interest to investigate how it is used by teachers in cooperation. The current article presents the results of the study ProZiTT (Processes of Cooperation in teamteaching), in which four teacher teams were filmed during their joint planning sessions and additionally surveyed with a questionnaire. The results obtained from qualitative content analysis and the questionnaire show that in team planning processes the potential for discharge is already used. The potential for enhancement of teachers’ professional level is however sparsely used. Reflection in team proved to be promising in this respect.